Radiotherapy after testis-sparing surgery for seminoma in monorchid patients: safety and efficacy. Issue 2 (April 2022) - Avuzzi, Barbara; Tittarelli, Andrea; Andreani, Stefano; Noris Chiorda, Barbara; Seregni, Ettore; Villa, Sergio; Tana, Silvia; Valdagni, Riccardo; Salvioni, Roberto; Biasoni, Davide; Catanzaro, Mario; Stagni, Silvia; et al.
Purpose: To evaluate local control and longitudinal endocrine data in monorchid patients treated with testicular-sparing surgery and adjuvant radiotherapy (RT) for seminomatous germ-cell tumors. Methods: We searched our database established in 2009 for patients with seminoma who received testis irradiation following partial orchiectomy up to 2018. Eleven patients were identified. All had associated germ cell neoplasia in situ (GCNIS) in surrounding parenchyma. Analysis focused on local control and testosterone levels preservation after RT. We considered age, baseline (pre-RT) testosterone and luteinizing hormone (LH) levels, residual testicular volume, tumor size, and testosterone and LH levels trend over time in order to identify any association with endocrine impairment leading to hormonal replacement need. Results: After a median follow-up of 21 months, no local or distant relapses were observed and hormonal function was maintained in 54.5% of patients (6/11). No significant interactions were observed for the investigated covariates. Notably, we observed an association between higher baseline testosterone levels and a decreased risk of exogenous androgen replacement (hazard ratio [HR] 0.409, 95% confidence interval [CI] 0.161–1.039, p = 0.060), whereas tumor size was associated with an increased risk of exogenous androgen replacement (HR 1.847, 95% CI 0.940–3.627, p = 0.075). Conclusions: Radiotherapy after testicular sparing surgery is effective in preventing local disease relapse in presence of GCNIS in the medium term. This strategy allows a preservation of adequate endocrine function in about half of patients. More patients and longer follow-up are needed to confirm these findings.